Effects of constant light exposure on sphingolipidomics and progression of NASH in high‐fat‐fed rats. Issue 11 (23rd February 2020) - Yue, Fangzhi; Xia, Ke; Wei, Lin; Xing, Lin; Wu, Shanyu; Shi, Ying; Lam, Sin Man; Shui, Guanghou; Xiang, Xingwei; Russell, Ryan; Zhang, Dongmei
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) is a growing public health concern worldwide. With the progression of urbanization, light pollution is becoming an inevitable risk factor for NAFLD. However, the role of light pollution on NAFLD is insufficiently understood, and the underlying mechanism remains unclear. The present study explored effects of constant light exposure on NAFLD and elucidated its related mechanisms. Methods: Thirty‐two male Sprague Dawley rats were divided into four groups ( n  = 8 each): (i) rats on a normal diet exposed to standard light–dark cycle (ND‐LD); (ii) rats on a normal diet exposed to constant light (ND‐LL); (iii) rats on a high‐fat diet exposed to standard light–dark cycle (HFD‐LD); and (iv) and rats on a high‐fat diet exposed to constant light (HFD‐LL). After 12 weeks of treatment, rats were sacrificed and pathophysiological assessments were performed. Targeted lipidomics was used to measure sphingolipids, including ceramides, glucosylceramides, and lactosylceramides, sphingomyelins, and sphingosine‐1‐phosphates in plasma and liver tissues. Results: In normal chow rats, constant light exposure led to glucose abnormalities and dyslipidemia. In high‐fat‐fed rats, constant light exposure exacerbated glucose abnormalities, dyslipidemia, insulin resistance, and inflammation and aggravated steatohepatitis. Compared with HFD‐LD rats, HFD‐LL had decreased plasma sphingosine‐1‐phosphate and elevated liver concentrations of total ceramide and specific ceramide species (ceramide d18:0/24:0, ceramide d18:1/22:0, ceramide d18:1/24:0, and ceramide d18:1/24:1), which were associated with increased hepatocyte apoptosis. Conclusions: Constant light exposure causes dysregulation of sphingolipids and promotes steatohepatitis in high‐fat‐fed rats.